Artistic freedom in international law - Polymenopoulou, Eleni (United Kingdom: Cambridge University Press, 2023)
'Lawyers interested in human rights, art law, cultural rights, cultural heritage law; artists and art students who want to know more about the legal framework applicable to arts ; free speech activists and human rights defenders; political scientists interested in global controversies such as Charlie Hebdo and the Danish Cartoons'--
Defining'art' -- The nature, scope and protection of artistic freedom -- Censorship and restrictions -- Positive obligations in relation to artistic freedom -- Street art, graffiti, and art in public space -- Public morality, obscenity, and the arts -- Blasphemous paintings, cartoons, and other religiously offensive art.
Puan Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 6393/ Pemilihan Ketua Perpustakaan Undang-Undang/ CIP/ Bookline Services
Includes bibliographical references and index. (221-225 pages)
Keywords: Law and art; Copyright -- Art; Art -- Censorship; Obscenity (Law); Freedom and art; Art and religion; Blasphemy -- Law and legislation; Artists -- Legal status, laws, etc